Financial literacy of households: theoretical aspects - Sitenko, D.A.; Gartsueva , Ye.V. (BUKETOV BUSINESS REVIEW, 2018)
The article deals with theoretical aspects of the financial literacy of households in a modern market economy. The authors consider financial literacy as an integral part of human capital, which determines the financial behavior of the individual. In the modern world, households are active participants in socio-economic relations, including financial ones. Each household decides on the funds at their disposal, participates in longterm insurance, mortgage and pension programs, which increases personal responsibility of citizens for their own financial decisions, economic well-being. Accordingly, the urgency of issues related to the financial literacy of households is growing. The article considers financial literacy as an element of the household's basic asset. The authors analyzed and summarized the views of researchers in this field, considered the concept of financial literacy in the narrow and broad sense of the word. The components, on which financial competence is measured, including financial awareness, are considered. Financial literacy helps households effectively plan and use their personal budgets, make decisions, in the field of personal finance, based on their long-term interests, recognize threats and reduce the risks of fraud.